Temperature analysis and comparison of active power losses in non-stationary and stationary thermal conditions of overhead power lines - V. M. Trotsenko (Омский научный вестник)
The article considers the temperature distribution with increased currents in the nonstationary thermal regime of overhead power lines. The temperature distribution along the length of the line for wires of AC-240/32 and G(Z)TACSR 240 grades is constructed. Temperature dependences on time are plotted. The practical value of the mathematical model considered in the article lies in determining the maximum temperatures of overhead lines of different sections in normal or post-emergency wire mode. A comparative analysis of active power losses in a stationary thermal regime is carried out with and without taking into account axial heat transfer. The comparison showed that taking into account the axial heat transfer refines the active power losses, which allows introducing measures to reduce these losses with greater accuracy.